Direct evidence on income comparisons and subjective well-being - Laszlo Goerke; Markus Pannenberg (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2013)
Subjective well-being (SWB) is generally argued to rise with relative income. However, direct evidence is scarce on whether and how intensively individuals undertake income comparisons, to whom they relate, and what they perceive their relative income to be. In this paper, novel data with direct information on income comparison intensity and perceived relative income with respect to predetermined reference groups is used to provide evidence on the relationship between income comparisons and SWB. We find negative correlations between comparison intensity and SWB for co-workers, people in the same occupation and friends. For job-related reference groups income comparisons are mostly upwards and perceiving to earn less than the reference group is negatively correlated with SWB.
Keywords: D31; D62; I31; 330; Income Comparisons; Endogenous Reference Groups; German Socio-Economic Panel (SOEP); Subjective Well-Being